2015
DOI: 10.1038/srep13203
|View full text |Cite
|
Sign up to set email alerts
|

Electronic control of coherence in a two-dimensional array of photonic crystal surface emitting lasers

Abstract: We demonstrate a semiconductor PCSEL array that uniquely combines an in-plane waveguide structure with nano-scale patterned PCSEL elements. This novel geometry allows two-dimensional electronically controllable coherent coupling of remote vertically emitting lasers. Mutual coherence of the PCSEL elements is verified through the demonstration of a two-dimensional Young’s Slits experiment. In addition to allowing the all-electronic control of the interference pattern, this type of device offers new routes to pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…HERE have been significant recent developments in photonic crystal surface emitting lasers [1,2], with a particular focus on increasing output power through the development of individual lasers [3,4] through photonic crystal design and through coherent laser arrays [5]. Recently, triangular PC features (on a square lattice) have been exploited to realize watt-level output powers [6].…”
Section: Introductionmentioning
confidence: 99%
“…HERE have been significant recent developments in photonic crystal surface emitting lasers [1,2], with a particular focus on increasing output power through the development of individual lasers [3,4] through photonic crystal design and through coherent laser arrays [5]. Recently, triangular PC features (on a square lattice) have been exploited to realize watt-level output powers [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PCSELs with high single mode power, low divergence [8], wavelength and polarisation control [9], have been experimentally demonstrated. We have also showed that coherent 2D PCSEL arrays may be readily realised [10], [11], and that external in-plane feedback significantly modifies the operating characteristics of a PCSEL [12].…”
Section: Introductionmentioning
confidence: 70%
“…Recently, PCSELs with high single mode power, low divergence [8], wavelength and polarisation control [9], have been experimentally demonstrated. We have also showed that coherent 2D PCSEL arrays may be readily realised [10], [11], and that external in-plane feedback significantly modifies the operating characteristics of a PCSEL [12]. Whilst experimental works has flourished, the theoretical development of PCSELs has been a daunting task.…”
Section: Introductionmentioning
confidence: 91%